Acute Liver Failure Secondary to Niacin Toxicity - Marc A. Ellsworth; Katelyn R. Anderson; David J. Hall; Deborah K. Freese; Robin M. Lloyd (Hindawi Limited, 2014)
A 17-year-old male was transferred to the pediatric intensive care unit for evaluation of acute liver failure. He was recently released from an alcohol treatment center with acute onset of chest pain. Cardiac workup was negative but he was found to have abnormal coagulation studies and elevated liver transaminases. Other evaluations included a normal toxicology screen and negative acetaminophen level. Autoimmune and infectious workups were normal providing no identifiable cause of his acute liver failure. He initially denied any ingestions or illicit drug use but on further query he admitted taking niacin in an attempt to obscure the results of an upcoming drug test. Niacin has been touted on the Internet as an aid to help pass urine drug tests though there is no evidence to support this practice. Niacin toxicity has been associated with serious multisystem organ failure and fulminant hepatic failure requiring liver transplantation. Pediatric providers should be aware of the risks associated with niacin toxicity and other experimental medical therapies that may be described on the Internet or other nonreputable sources.